1992
DOI: 10.1051/kmae:1992003
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs biologiques à prendre en compte dans la conception des ouvrages de franchissement, notions d'obstacles à la migration

Abstract: La propulsion de la plupart des espèces dans leur activité de migration (en particulier le franchissement des obstacles) est assurée par l'ondulation du corps et de la nageoire caudale.Des expérimentations (WARDLE, 1975) ont montré que la distance parcourue (A) par le poisson à chaque ondulation du corps peut varier entre 0.6 et 0.8 fois sa longueur (L). La vitesse de nage peut donc s'exprimer sous la forme : CHAPITRE 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…Some brown trout leaps observed were superior to theoretical leaping capacity of the species (Beach 1984). These results confirm that the theoretical trajectories do not take into account the actual hydraulic heterogeneity used by fish, such as the velocity at the foot of a drop as well as the additional propulsive force cause by the beating caudal fins at the moment it leaves the surface of the water (Larinier 1992). Furthermore, the theoretical curves do not consider microhabitat conditions that fish probably exploit.…”
Section: Discussionsupporting
confidence: 58%
“…Some brown trout leaps observed were superior to theoretical leaping capacity of the species (Beach 1984). These results confirm that the theoretical trajectories do not take into account the actual hydraulic heterogeneity used by fish, such as the velocity at the foot of a drop as well as the additional propulsive force cause by the beating caudal fins at the moment it leaves the surface of the water (Larinier 1992). Furthermore, the theoretical curves do not consider microhabitat conditions that fish probably exploit.…”
Section: Discussionsupporting
confidence: 58%
“…The survival rates estimated in this study are in the upper limit of the range reported for rainbow trout of similar size (Normandeau Associates, Inc. 2002) and for other fish species passing through Francis turbines (Davies 1988;Eicher and Associates, Inc. 1987;Larinier and Dartiguelongue 1989;Bell 1990;Winchell et al 1992;Larinier 1992) and similar to survival rates through larger Kaplan turbines (Mathur et al 1996). Why the survival rates estimated in this study were so high is unclear.…”
Section: Discussionsupporting
confidence: 45%